Facial palsy after dental procedures – Is viral reactivation responsible?. Issue 1 (January 2017) - Gaudin, Robert A.; Remenschneider, Aaron K.; Phillips, Katie; Knipfer, Christian; Smeets, Ralf; Heiland, Max; Hadlock, Tessa A.
Abstract: Objectives: Herpes labialis viral reactivation has been reported following dental procedures, but the incidence, characteristics and outcomes of delayed peripheral facial nerve palsy following dental work is poorly understood. Herein we describe the unique features of delayed facial paresis following dental procedures. Materials and methods: An institutional retrospective review was performed to identify patients diagnosed with delayed facial nerve palsy within 30 days of dental manipulation. Demographics, prodromal signs and symptoms, initial medical treatment and outcomes were assessed. Results: Of 2471 patients with facial palsy, 16 (0.7%) had delayed facial paresis following ipsilateral dental procedures. Average age at presentation was 44 yrs and 56% (9/16) were female. Clinical evaluation was consistent with Bell's palsy in 14 (88%) and Ramsay-Hunt syndrome in 2 patients (12%). Patients developed facial paresis an average of 3.9 days after the dental procedure, with all individuals developing a flaccid paralysis (House Brackmann (HB) grade VI) during the acute stage. 50% of patients developed persistent facial palsy in the form of non-flaccid facial paralysis (HBIII-IV). Conclusion: Facial palsy, like herpes labialis, can occur in the days following dental procedures and may also be related to viral reactivation. In this small cohort, long-term facial outcomes appear worse than for spontaneous Bell's palsy.